2013
DOI: 10.1155/2013/238351
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Gelatin Nanoparticles for Drug Delivery to the Ocular Surface: In Vitro and In Vivo Evaluation

Abstract: To develop an effective ocular drug delivery carrier, we prepared two different charged gelatin nanoparticles (GPs) and evaluated particle size, surface charge, and morphology. The in vitro biocompatibility of GPs was assessed using human corneal epithelium (HCE) cells and in vivo safety by administering them as eye drops to New Zealand rabbits. The GPs prepared using type A gelatin were positively charged (GP(+), +33 mV; size, 180.6 ± 45.7 nm). Water-soluble tetrazolium salt (WST)-1 assay showed that both GPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…36 Our previous study showed that cationic gelatin NPs (GNPs) can be attracted to rabbit cornea and retained in the cornea for a longer time. 38 Therefore, GNPs with positive charge are promising as vehicles for ocular drug delivery.…”
mentioning
confidence: 99%
“…36 Our previous study showed that cationic gelatin NPs (GNPs) can be attracted to rabbit cornea and retained in the cornea for a longer time. 38 Therefore, GNPs with positive charge are promising as vehicles for ocular drug delivery.…”
mentioning
confidence: 99%
“…For instance, the cornea and conjunctiva possess negative surface charges, and it is expected that the cationic colloidal NPs can enhance the retention time on negatively charged ocular tissues more efficiently than the anionic carriers, providing an increased opportunity for the drug to enter the eye [ 37 ]. Tseng et al 2013, proved that the topical administration of positively charged gelatin nanoparticles could prolong the drug retention time on the negatively charged ocular surface, compared to the free-form drug formulation [ 38 ]. Xu et al 2013, found that NPs coated with different surface charges of polyethylene glycol (PEG) resulted in a variant delivery efficacy in an ex vivo model of the bovine vitreous body.…”
Section: Advantages Of Nanocarriers For Ocular Drug Deliverymentioning
confidence: 99%
“…Thanks to the high biocompatibility shown, several examples of gelatin NPs intended for ophthalmic use can be found in the literature. Gelatin allows the preparation of both positive and negative NPs, with smooth surface and spherical shape [97], to be administered either topically [97,98] or intra-vitreally [68] and loaded with small molecules [98] as well as with high molecular weight compounds [68]. In order to increase ocular bioavailability of pilocarpine HCl and hydrocortisone, two drugs with different solubility, they were encapsulated in gelatin NPs via desolvation method [98].…”
Section: Carrier Proteinsmentioning
confidence: 99%
“…Since the ocular surface is negatively charged, because of the presence of sialic acid residues in the mucus, some authors suggested that cationic NPs may better interact and/or penetrate cornea and conjunctiva than the anionic ones [97,99]. For this reason, cationic gelatin NPs were prepared and loaded with a plasmid designed to encode human MUC5AC [100].…”
Section: Carrier Proteinsmentioning
confidence: 99%